Exploring the effects of Sheffield’s clean air zone on air quality and traffic volume - Guto Williams; Harry Kai-Ho Chan; Patricio Ortiz (Environmental Research Communications)
In the UK, poor air quality is estimated to contribute to 36,000 deaths annually. Since 2021 local authorities have introduced Clean Air Zones (CAZs) to tackle the pollution caused by road traffic. These aim to improve air quality within the CAZ by deterring high polluting vehicles from entering. As of August 2024, there were seven CAZs active in England. This work focuses on Sheffield, UK and explore how the implementation of the CAZ has affected air quality in the city. The impact of Sheffield’s CAZ on NO _2 and PM _2.5 was assessed with data sourced from three DEFRA sites within Sheffield. Weather normalisation was conducted to isolate the impacts of weather. Then the impact of Sheffield’s CAZ was evaluated using a Difference-in-Difference (DiD) method. The changes in traffic following the CAZ were also evaluated to assess the potential for spillover. Our results showed that reductions in air pollutions happen both inside and outside the CAZ, but neither PM _2.5 or NO _2 were significantly reduced within the CAZ. There were no signs of negative spillover with only 5 out of the 33 traffic sensors (16%) showing an increase in traffic post-CAZ. The results were generally in line with the studies on London’s ULEZ and Birmingham’s CAZ that showed no significant changes in PM _2.5 and small changes in NO _2 . This work differs from literature by suggesting that the CAZ did not drive this NO _2 reduction, with NO _2 concentrations reducing both inside and outside the CAZ. This was likely down to fleet modernisation, with the proportion of non-compliant vehicles across Sheffield reducing by 18% post-CAZ. This highlights how CAZ may be one policy implemented to improve air quality with multiple policies working in conjunction to reduce air pollution.